CellDestiny: A RShiny application for the visualization and analysis of single-cell lineage tracing data - Hadj Abed, Louisa; Tak, Tamar; Cosgrove, Jason; Perié, Leïla (Frontiers in Medicine, 2022)
Single-cell lineage tracing permits the labelling of individual cells with a heritable marker to follow the fate of each cell’s progeny. Over the last twenty years, several single-cell lineage tracing methods have emerged, enabling major discoveries in developmental biology, oncology and gene therapies. Analytical tools are needed to draw meaningful conclusions from lineage tracing measurements, which are characterized by high variability, sparsity and technical noise. However, the single cell lineage tracing field lacks versatile and easy-to-use tools for standardized and reproducible analyses, in particular tools accessible to biologists. Here we present CellDestiny, a RShiny app and associated web application developed for experimentalists without coding skills to perform visualization and analysis of single cell lineage-tracing datasets through a graphical user interface. We demonstrate the functionality of CellDestiny through the analysis of (i) lentiviral barcoding datasets of murine hematopoietic progenitors (ii) published integration site data from Wiskott-Aldrich Symdrome patients undergoing gene-therapy treatment and (iii) simultaneous barcoding and transcriptomic analysis of murine hematopoietic progenitor differentiation in vitro. In summary, CellDestiny is an easy-to-use and versatile toolkit that enables biologists to visualize and analyse single-cell lineage tracing data.